Study of Hibiscus tiliaceus Leaf Extract Carrier as Additive in the Diets for Fattening of Local Cattle (in vitro) - Bata, Muhamad; Rahayu, Sri (Pakistan Journal of Nutrition, 2016)
Objective: The purpose of this study was to find the type of Hibiscus tiliaceus leaf extract carrier for improving the fermentation products and ruminal metabolism efficiency. Methodology: This study was designed according to completely randomized design with 3×2 factorial patterned and repeated three times. The first factor was the type of feed ingredients as carrier such as cassava waste meal, rice bran and rice straw ammoniated and the second factor was the doses of Hibiscus tiliaceus extract i.e., 0 and 200 ppm. Results: Analysis of variance showed that additional leaf extract of H. tiliaceus with various carrier materials (cassava waste meal, rice bran and rice straw ammoniated) did not affect (p>0.05) on the total protozoa, microbial protein synthesis, fermentation product and activity of hydrolytic enzymes in rumen liquid. However, additional H. tiliaceus leaf extract at 200 ppm tended to reduce total protozoa, but total VFA and the activity of rumen amylase, protease and cellulase increased. Feedstuff with higher capacity to reduce protozoa population and to increase VFA and enzyme activity was rice bran. Cassava waste meal, rice bran and ammoniated wheat straw can be used as carrier of ethanolic extracts of H. tiliaceus leaf. Conclusion: This study recommended that rice bran as carrier for in vivo application due to the defaunation effects of rumen protozoa and high hydrolytic enzymes activity in the rumen.